2008
DOI: 10.1016/j.pbiomolbio.2008.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of human atrial cell models: Restitution, memory, and intracellular calcium dynamics in single cells

Abstract: Mathematical models of cardiac cells have become important tools for investigating the electrophysiological properties and behavior of the heart. As the number of published models increases, it becomes more difficult to choose a model appropriate for the conditions to be studied, especially when multiple models describing the species and region of the heart of interest are available. In this paper, we will review and compare two detailed ionic models of human atrial myocytes, the Nygren et al. model (NM) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 36 publications
5
57
1
Order By: Relevance
“…Single cell simulations were conducted using the forward Euler method with time step of 0.02 ms. Figure 1 shows the time course of the steady-state AP and the main underlying ionic currents in control and AFER atrial cardiomyocytes, using the MGGT model (left) and the CRN model (right). In both models, AFER results in shortening of APD 90 and slight RMP hyperpolarization, consistent with previous experimental and theoretical human atrial studies (6,12,50). Steady-state APD 90 shortens from 200 ms in control to 115.8 ms in AFER in simulations using the MGGT model and from 252 ms to 115.5 ms using the CRN model.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…Single cell simulations were conducted using the forward Euler method with time step of 0.02 ms. Figure 1 shows the time course of the steady-state AP and the main underlying ionic currents in control and AFER atrial cardiomyocytes, using the MGGT model (left) and the CRN model (right). In both models, AFER results in shortening of APD 90 and slight RMP hyperpolarization, consistent with previous experimental and theoretical human atrial studies (6,12,50). Steady-state APD 90 shortens from 200 ms in control to 115.8 ms in AFER in simulations using the MGGT model and from 252 ms to 115.5 ms using the CRN model.…”
Section: Methodssupporting
confidence: 88%
“…Finally, a few recent studies have focused on the comparison of different AP models aiming at targeting similar cell type and mammalian species and have highlighted differences in dynamics because of differences in the model equations and parameters (7,11,12,13,58,59). The results of this study should be interpreted with caution since there could be different combinations of changes in the model parameters leading to similar results (62).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For each pacing location, an S1-S2 extra stimulus protocol was applied. A wide-area S1 stimulus of 50µΑ/mm 3 was followed 315 ms later by a second smaller S2 stimulus of strength 100µΑ/mm 3 on the boundary of the S1 stimulus to initiate two counter-rotating spiral waves. The area of the S1 Figure 2.…”
Section: Simulation Protocolmentioning
confidence: 99%
“…A rotor is defined as a high frequency curved wavefront, which meets the wavetail at a single point and is characterised by the absence of refractory tissue at the centre [2]. Until recently, the presence of rotors was only observed in animal experimental studies [3], but localized and stable rotors in human AF have now been identified [4,5]. This progress may increase the efficacy of targeted left atrial ablation therapy.…”
Section: Introductionmentioning
confidence: 99%